(untitled) (#schuleverantworten, 2021)
This paper describes the inquiry-oriented improvement concept of CrEEd for Schools regarding pivotal characteristics, prototypical experiences, and findings concerning its impact on pupils’ learning experience and teachers’ instructional performance. A reflection of these experiences and findings collected during an implementation process conducted in an Austrian secondary school (2018–2019), motivates us to further rethink and to extend the conceptual architecture of CrEEd for Schools. We adjusted decisive conceptual components and integrated a concrete content layer into this inquiry-oriented approach – namely the sustainable development goals (SDGs). In doing so, we assume that the revised concept CrEEd for Future Schools will overcome the initial obstacles.